Cognitive abilities of institutionalized older persons with depressive symptoms - Felício,Laís Francielle Francisca (2022)
ABSTRACT Objective To determine the level of association between depressive symptoms and cognitive abilities of institutionalized older adults. Methods This is a cross-sectional study that enrolled 69 older adults, living in a long-term care facility. Investigation of depressive symptoms in all individuals was performed using the geriatric depression scale. Cognitive verbal fluency, digit span forward (DSF) and backward (DSB) tests, and two-minute stationary gait, sit-to-stand test, and six-minute walk test were performed to assess their association with depressive symptoms. Results Depressive symptoms were identified in 35 individuals. Worse cognition and physical performances were associated with the presence of depressive symptoms – Mini-Mental State Examination [t (61) = 2.36; p < 0.05] and Stationary gait test of two minutes [t (53) = 3.12; p < 0.05]. Short-term memory and working memory tests presented worse results in individuals with depressive symptoms (DSF: U = 402.00; p < 0.05 e DSB: U = 341,00; p < 0.05). Older adults with scores below normal in DSF were 5 times more likely to exhibit depressive symptoms. Conclusion The importance of physical, cognitive and social intervention strategies in long-term care facilities for the older adults is highlighted, in order to privilege autonomy. Notably, there is an association between deficits in short-term memory and the presence of depressive symptoms in older adults. Therefore, prospective studies are suggested to investigate the cause-effect relationship of this association with the institutionalization of older adults.